Advances in Italian Robotics - Boschetti, Giovanni; Rosati, Giulio; Carbone, Giuseppe (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book disseminates the latest research achievements, findings, and ideas in the robotics field, with particular attention to the Italian scenario. Book coverage includes topics that are related to the theory, design, practice, and applications of robots, such as robot design and kinematics, dynamics of robots and multi-body systems, linkages and manipulators, control of robotic systems, trajectory planning and optimization, innovative robots and applications, industrial robotics, collaborative robotics, medical robotics, assistive robotics, and service robotics. Book contributions include, but are not limited to, revised and substantially extended versions of selected papers that have been presented at the 2nd International Conference of IFToMM Italy (IFIT 2018).